740. Impact of the 2014 American Academy of Pediatrics Guidance on Respiratory Syncytial Virus Hospitalization Rates for Preterm Infants <29 Weeks Gestational Age at Birth: 2012–2016. (26th November 2018) - Goldstein, Mitchell; Krilov, Leonard R; Fergie, Jaime; Brannman, Lance; Ambrose, Christopher S; Wade, Sally; Kong, Amanda
Abstract: Background: In 2014, the American Academy of Pediatrics stopped recommending RSV immunoprophylaxis (RSV IP) for otherwise healthy infants 29–34 weeks gestational age (wGA), while continuing to recommend RSV IP for infants born at <29 wGA. The decline in RSV IP and associated increase in RSV hospitalizations (RSVH) among infants 29–34 wGA have been described previously, but potential effects of the 2014 guidance change on preterm infants <29 wGA are unknown. This study compared 2012–2014 and 2014–2016 outpatient RSV IP use as well as RSVH rates relative to term infants among otherwise healthy <29 wGA infants. Methods: Infants born from July 1, 2011 to June 30, 2016 were followed from birth hospitalization discharge through their ﬁrst year of life in the MarketScan Commercial (COM) and Multistate Medicaid (MED) databases. DRG and ICD codes identified term and <29 wGA infants at birth. RSV IP receipt was derived from pharmacy and outpatient medical claims (inpatient RSV IP data were unavailable). RSVH were derived from inpatient medical claims. RSVH IP use and RSVH were assessed across three chronologic age (CA) groups: <3 months, 3–<6 months, and 6–<12 months. RSVH rate ratios for 2012–2014 and 2014–2016 were calculated for <29 wGA infants using healthy term infants 0–<12 months of age as a reference category. Results: Outpatient RSV IP receipt fell after 2014 for <29 wGA infants across all CA categories, with the greatest decline observed among infants <3 months CA (Table 1). Greater RSVH rates for <29 wGA infants relative to term infants were observed after 2014 (Figures 1 and 2), with infants <3 months CA experiencing the greatest percentage increases in relative RSVH risks. Conclusion: Outpatient RSV IP decreased and RSVH relative to term infants increased among otherwise healthy <29 wGA infants following the 2014 policy change, even though RSV IP continued to be recommended. The effects were greatest for infants <3 months CA and those insured by Medicaid. Funded by AstraZeneca Disclosures: M. Goldstein, AstraZeneca/MedImmune: Consultant, Research grant and Research support. L. R. Krilov, AstraZeneca/MedImmune: Consultant, Research grant and Research support. J. Fergie, AstraZeneca/MedImmune: Consultant and Speaker's Bureau, Research grant and Research support. L. Brannman, AstraZeneca: Employee, Salary and Stocks. C. S. Ambrose, AstraZeneca: Employee, Salary and Stocks. S. Wade, Wade Outcomes Research and Consulting contracted by Truven: Consultant, Consulting fee. A. Kong, Truven Health Analytics, an IBM Company: Employee, Salary.